Identités Postcoloniales Et Racisme Dérivatif Selon Frantz Fanon - ANY Hobido Désiré (European Scientific Journal, ESJ, 2016)
This article analyses a nodal difficulty which leads the postcolonial African countries in the dead end. It erects the hypothesis that in Africa, the construction of postcolonial identities leads to a derivative racism-labeled by the birth of the burgess state. Instead of building nation-state, the political leaders create burgess ones, without productive tracts but which favor a chauvinistic nationalism. The dialectic of the emancipation of Africa is not accomplished then. That is why Fanon extols the emergence of the rescuer ideology of Africa. What is about? What are its stakes, its bearings and its limit? This article will help us to answer these questions.